2001
DOI: 10.1093/jnci/93.19.1465
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Nonpromoter CpG Islands to De Novo Methylation in Normal and Neoplastic Cells

Abstract: The methylation patterns that we observed suggest that exonic CpG islands are more susceptible to de novo methylation than promoter islands and that methylation may be seeded in exonic regions, from which it can spread to other islands, including promoter regions. Subsequent selection of cells with a growth advantage conferred by spread of methylation into and inactivation of a particular promoter might then contribute to the genesis of a specific type of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 20 publications
8
76
0
1
Order By: Relevance
“…Methylation of p15 was associated with relapsed ALL patients (Garcia-Manero et al, 2002a), suggesting it might be a late event in the progression of ALL. In AML patients, methylation of p15 gene was demonstrated in 45% of patients which was within the range of previous reports (32-93%) (Melki et al, 1999;Guo et al, 2000;Wong et al, 2000;Wu et al, 2000;Chim et al, 2001;Dodge et al, 2001;Nguyen et al, 2001;Chim et al, 2003;Christiansen et al, 2003;Ekmekci et al, 2004;Galm et al, 2005;Olesen et al, 2005;Shimamoto et al, 2005;El-Shakankiry and Mossallam, 2006;Griffiths et al, 2010;Kurtovic et al, 2012). Previously, low RNA levels of p15 were reported in AML (Schwaller et al, 1997) which was also correlated with methylation of this gene (Matsuno et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Methylation of p15 was associated with relapsed ALL patients (Garcia-Manero et al, 2002a), suggesting it might be a late event in the progression of ALL. In AML patients, methylation of p15 gene was demonstrated in 45% of patients which was within the range of previous reports (32-93%) (Melki et al, 1999;Guo et al, 2000;Wong et al, 2000;Wu et al, 2000;Chim et al, 2001;Dodge et al, 2001;Nguyen et al, 2001;Chim et al, 2003;Christiansen et al, 2003;Ekmekci et al, 2004;Galm et al, 2005;Olesen et al, 2005;Shimamoto et al, 2005;El-Shakankiry and Mossallam, 2006;Griffiths et al, 2010;Kurtovic et al, 2012). Previously, low RNA levels of p15 were reported in AML (Schwaller et al, 1997) which was also correlated with methylation of this gene (Matsuno et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…In CLL patients, methylation of p15 was observed in 19% of subjects. Previous studies reported 9-36% methylation in p15 (Nguyen et al, 2001;Chim et al, 2006a;Seeliger et al, 2009). In the present study, methylation in p15 gene was seen in all types of leukemia, however it was most frequent in AML (45% of cases).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This is in line with the hypothesis that exonic CpG islands are most susceptible for de novo methylation. 26 Thus, hypermethylation of the paternal allele might initiate in CpG island III and then spread to CpG island I near the promoter region (Fig. 1b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were probably influenced by the use of the CpG methylation-sensitive NotI for the DNA digestion because NotI preferentially cleaves in CpG-rich regions of the mammalian genome. Cancer-associated hypermethylation is seen in CpG islands distant from the 5' end of the gene Nguyen et al, 2001a) as well as in those that straddle the transcription start site. Therefore, the observed prevalence of cancer-linked hypermethylation in 5' CpG islands may be due to an ascertainment bias.…”
Section: Types Of Sequences Affected By Cancer-associated Hypermethylmentioning
confidence: 99%